An overview of ecological traps in marine ecosystems. Issue 4 (9th March 2021) - Swearer, Stephen E; Morris, Rebecca L; Barrett, Luke T; Sievers, Michael; Dempster, Tim; Hale, Robin
Abstract : Humans are altering marine ecosystems at unprecedented rates, and these changes can result in animals selecting poor‐quality habitats if the cues they use become misleading. Such "ecological traps" increase extinction risk, reduce ecosystem resilience, and are a consequence of human‐induced rapid environmental change. Although there is growing evidence for traps impacting terrestrial species, the phenomenon has so far received little attention from marine scientists. To explore why so few studies have attempted to identify traps in the ocean, we conducted a literature review of the major drivers of marine environmental change to determine how their impacts on habitat choice and species fitness are being assessed. From this we summarize the current evidence for marine traps, present case studies to show why the phenomenon is potentially common in the ocean, highlight ways to advance awareness and understanding of traps, and demonstrate how this information can help improve management of marine environments.